Addition of L-tyrosine to improve betalain production in red pitaya callus - Abu Faizal, Nor Fadzliana; Sekeli, Rogayah; Shaharuddin, Noor Azmi; Abdullah, Janna Ong (Universiti Putra Malaysia Press, 2017)
The aim of this study is to enhance betalain production in red pitaya (Hylocereus polyrhizus) callus through supplementation of the precursor L-tyrosine. Red-pigmented calli were produced on Murashige and Skoog (MS) basal salt medium supplemented with 2 mg/L naphthaleneacetic acid (NAA), 4 mg/L thidiazuron (TDZ) and different concentrations of L-tyrosine (20, 40, 60, 80, 100 mg/L). The addition of 20 mg/L L-tyrosine was able to increase betacyanin production by 1.5-fold compared to calli grown on Murashige and Skoog (MS) basal salt medium (MSO). The results also revealed that betalain production (calli cultured with 20 mg/L L-tyrosine) was higher than MS medium with 2 mg/L NAA and 4 mg/L TDZ (without L-tyrosine) up to 1.7-fold. Four compounds, namely betacyanin, betaxanthin and two additional compounds, phenolic and flavonoid compounds, were detected in the red-pigmented calli treated with 20 mg/L L-tyrosine that were not found in the fresh fruit sample. This indicates that the callus system has potential to produce betalain pigment and that red-pigmented calli could be an important antioxidant source.